Studies on in Vitrro assessment of "drug resistance" in trypanosoma vivax. - Kitosi, D.S. (University of Nairobi, 1990)
Six stocks of Trypanosoma vivax were investigated for their drug sensitivity to isometamidium chloride and diminazene aceturate. It was evaluated whether in vitro tests had the potential to distinguish between drug-sensitive and drug-resistant stocks of T vivax. Four in vitro tests were employed in drug sensitivity assessment: (1) Long Term Viability Assay (20 days) with insect forms at 27 C, (2) 3H-Hypoxanthine Incorporation Test (48 hrs) with bloodstream forms at 340C, (3) Drug Incubation Infectivity Test (DIIT) with bloodstream forms at 370C and (4) Drug Incubation Survival Test with bloodstream forms at 340C. All tests were able to show an antitrypanosomal effect of both, isometamidium chloride and diminazene aceturate on T vivax in vitro. The antitrypanosomal effects were detected by rounding and death of epimastigotes, inhibition of 3H-Hypoxanthine incorporation by bloodstream forms, loss of infectivity to mice and reduction in the number of survivors. The Long Term Viability Assay and the Drug Incubation Survival Test showed potential to distinguish between isometamidium chloride-sensitive and isometamidium chloride-resistant stocks or clones . of T vivax. Results on drug sensitivity of T vivax stocks obtained with these tests correlated with results in cattle or mice. A correlation between in vitro and in vivo results was not observed regarding diminazene aceturate. When cattle were infected with in vitro produced metacyclics, resistance of bloodstream forms of T vivax stock CP 2171 was retained to treatment with 0.5 and 1.0 mg/kg isometamidium chloride after continuous in vitro propagation of epimastigotes for 30 months. The reduced sensitivity of epimastigotes of CP 2171 to isometamidium in vitro was similar in cultures initiated from these cattle compared with results obtained in cultures initiated from cattle infected with the original stabilate.